# (3x-4y)(3x-4y)=

## Simple and best practice solution for (3x-4y)(3x-4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (3x-4y)(3x-4y)= equation:

Simplifying
(3x + -4y)(3x + -4y) = 0
Multiply (3x + -4y) * (3x + -4y)
(3x * (3x + -4y) + -4y * (3x + -4y)) = 0
((3x * 3x + -4y * 3x) + -4y * (3x + -4y)) = 0
Reorder the terms:
((-12xy + 9x2) + -4y * (3x + -4y)) = 0
((-12xy + 9x2) + -4y * (3x + -4y)) = 0
(-12xy + 9x2 + (3x * -4y + -4y * -4y)) = 0
(-12xy + 9x2 + (-12xy + 16y2)) = 0
Reorder the terms:
(-12xy + -12xy + 9x2 + 16y2) = 0
Combine like terms: -12xy + -12xy = -24xy
(-24xy + 9x2 + 16y2) = 0
Solving
-24xy + 9x2 + 16y2 = 0
Solving for variable 'x'.
Factor a trinomial.
(3x + -4y)(3x + -4y) = 0
Subproblem 1Set the factor '(3x + -4y)' equal to zero and attempt to solve:
Simplifying
3x + -4y = 0
Solving
3x + -4y = 0
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
3x + -4y + 4y = 0 + 4y
Combine like terms: -4y + 4y = 0
3x + 0 = 0 + 4y
3x = 0 + 4y
Remove the zero:
3x = 4y
Divide each side by '3'.
x = 1.333333333y
Simplifying
x = 1.333333333y
Subproblem 2Set the factor '(3x + -4y)' equal to zero and attempt to solve:
Simplifying
3x + -4y = 0
Solving
3x + -4y = 0
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
3x + -4y + 4y = 0 + 4y
Combine like terms: -4y + 4y = 0
3x + 0 = 0 + 4y
3x = 0 + 4y
Remove the zero:
3x = 4y
Divide each side by '3'.
x = 1.333333333y
Simplifying
x = 1.333333333ySolutionx = {1.333333333y, 1.333333333y}`